Compensating for choroid plexus based off-target signal in the hippocampus using 18 F-flortaucipir PET - Pawlik, Daria; Leuzy, Antoine; Strandberg, Olof; Smith, Ruben (NeuroImage (Orlando, Fla.), 2020)
The hippocampus is affected by tau pathology early in Alzheimer's disease (AD) development. Accurate quantification of hippocampal tau signal using the tau-PET tracer F-flortaucipir is complicated, however, by off-target binding in the adjacent choroid plexus. We here present a new method for compensating for this off-target choroid plexus signal. As off-target binding in the choroid plexus is known to be higher using F-flortaucipir compared to F-RO948, we created a binary hippocampal mask in template space where F-flortaucipir signal was higher than F-RO948, using data from 30 patients that underwent both F-flortaucipir and F-RO948 PET. This mask, presumably representing hippocampal voxels affected by off-target binding from the choroid plexus, was then converted to native space and applied as an exclusion mask to 145 patients across the AD-spectrum scanned with F-flortaucipir. As an alternative approach exclusion masks were generated by expanding the choroid plexus ROI in native space. Results were analysed both without and with partial volume error correction (non-PVEc/PVEc). Unmasked hippocampal standardized uptake value ratios (SUVR) were significantly correlated to choroid plexus SUVRs using both non-PVEc (p < 0.001, r = 0.28) and PVEc data (p < 0.05, r = 0.18). After applying the mask, however, these correlations disappeared. The diagnostic accuracy in separating cognitively impaired (CI) from cognitively unimpaired (CU) subjects improved after masking, from an AUC of 0.792 (95% C.I.,0.715-0.869) to 0.837 (95% C.I.,0.768-0.906) for non-PVEc data (p < 0.001), and from 0.798 (95% C.I.,0.722-0.873) to 0.834 (95% C.I.,0.766-0.903) for PVEc data (p < 0.001). The correlations to memory improved significantly for MMSE for unmasked vs. masked data both without (r = -0.440 vs. r = -0.499, p < 0.001) and with (r = -0.454 vs. r = -0.503, p < 0.001) PVEc. Similar results were found using the ADAS-Cog Delayed Word Recall test. Choroid plexus off-target binding interferes with the estimation of true hippocampal retention using F-flortaucipir PET. Using a mask to correct for this off-target signal, we improved the diagnostic accuracy of F-flortaucipir in the hippocampus and the correlation between F-flortaucipir hippocampal SUVR and cognitive measures.